Association of vitamin D deficiency and premature coronary artery disease - Hamidreza Norouzi; Naghmeh Ziaie; Mehrdad Saravi; Alireza Norouzi; Somayye Noei; Fazilat Jokar darzi; Fatemeh Norouzi; Maede Rajabi fumashi; Farbod Zahedi tajrishi; Shahram Norouzi (Caspian Journal of Internal Medicine, 2019)
Background: Evidence suggests hypovitaminosis D is associated with increased risk of coronary artery disease (CAD) and its extent and related risk factors. However, some investigations have produced contrary results. Therefore, we aimed to evaluate the association between serum vitamin D levels and the severity of premature coronary artery involvement. Methods: This randomized prospective, case-control study was conducted in Babol from April 2013 to June 2017. We collected the demographic data and measured serum 25-OH-D levels of 294 patients (age≤50 years) diagnosed with CAD with coronary angiography as case group as well as 438 age and sex-matched controls. CAD severity was assessed using the Gensini score. Statistical analyses were used to assess the associations and p<0.05 was considered as significant. Results: The mean serum level of 25-OH-D was 13.12±11.13 and 18.28±8.34 in case and control groups, respectively (P=0.036). In the case group, mean serum vitamin D levels were significantly lower among hypertensives (P=0.018), those with a family history of CVD (P=0.016) and those who used aspirin (P=0.036). The mean Gensini score of patients in the case group was 45.02±23.62 and was higher among men (P=0.022). There was a weak significant correlation between the serum vitamin D levels and the Gensini score (P=0.001 & R=-0.543). The mean Gensini score was not significantly different between patients with deficient (47.02±22.78), insufficient (26.0±21.72) and sufficient (39.0±43.84) vitamin D levels (P>0.05). Conclusion: The results showed that the lower levels of vitamin D is associated with increased risk and extent of coronary artery involvement as well as some of the risk factors of CAD, including male gender, hypertension and positive family history for CVD.